Organized Crimes Against Nature: Elephants in Southern Africa. - Lopes, Adrian (2015)
Poaching of elephants in Southern Africa is now dominated by international groups following a model of organized crime. This shift, from poaching conducted by small, local groups; with limited mobility, weapons, and technology, to individuals who organize, finance, equip, and transport well-armed poaching units to previously scouted locations, has made the protection of elephants in Southern Africa much more difficult and dangerous. This paper develops a model of high-tech criminal poaching. A poaching organization makes a decision on the number of “planned poaching expeditions.” If a poaching unit is intercepted the entire organization is destroyed, but is replaced by a new organization in the next year. The operating life of a poaching organization is a stochastic process, which in turn induces a stochastic evolution in the elephant population. Under plausible conditions, the number of planned poaching expeditions is highly sensitive to the probability of interception by anti-poaching patrols, but is nonresponsive to reductions in the black-market ivory price. Thereby it might be better to focus conservation efforts on increasing the probability of intercepting poaching units rather than trying to control black market ivory prices. A benchmark value of poaching expeditions is identified—above which elephants may slowly decline to extinction.